THE EFFECT OF WORK ENVIRONMENT AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AT PT PLN (PERSERO) UP2D MAKASSAR - Nur Rosida Junaidi; Mahlia Muis; Andi Reni (Sean Institute, 2023)
This study aims to determine the effect of leadership style and environment on employee performance through work motivation at PT PLN (Persero) UP2D Makassar. Data analysis is the process of decomposing the whole into smaller components to find out the dominant feature, compare one element to another, and compare one or several of them to the whole. Techniques for data analysis are used to answer the problem formulation and test the existing hypothesis formulation. In this study, the data management used is SMARTPLS Software. The sample in this study were employees at the State Electricity Company (PLN) UP2D Makassar with a total sample of 75 people. The sampling technique in this study is purposive sampling. In this research, the type of data collected is primary data with data collection techniques, namely observation, interviews and questionnaires. The test results of Leadership Style have a positive effect on Employee Performance. The results of testing the H2 hypothesis Leadership Style positively affects Work Motivation. The results of testing the H3 hypothesis show that the work environment positively affects employee performance. The results of testing the H4 hypothesis indicate that the work environment positively affects work motivation. The results of testing the H5 hypothesis indicate that work motivation has no significant effect on employee performance. The results of testing the H6 hypothesis which shows that Leadership Style has no significant effect on Employee Performance through Work Motivation. The results of testing the H7 hypothesis indicate that the work environment does not significantly affect employee performance through work motivation. This study aims to determine the effect of leadership style and environment on employee performance through work motivation at PT PLN (Persero) UP2D Makassar. Data analysis is the process of decomposing the whole into smaller components to find out the dominant feature, compare one element to another, and compare one or several of them to the whole. Techniques for data analysis are used to answer the problem formulation and test the existing hypothesis formulation. In this study, the data management used is SMARTPLS Software. The sample in this study were employees at the State Electricity Company (PLN) UP2D Makassar with a total sample of 75 people. The sampling technique in this study is purposive sampling. In this research, the type of data collected is primary data with data collection techniques, namely observation, interviews and questionnaires. The test results of Leadership Style have a positive effect on Employee Performance. The results of testing the H2 hypothesis Leadership Style positively affects Work Motivation. The results of testing the H3 hypothesis show that the work environment positively affects employee performance. The results of testing the H4 hypothesis indicate that the work environment positively affects work motivation. The results of testing the H5 hypothesis indicate that work motivation has no significant effect on employee performance. The results of testing the H6 hypothesis which shows that Leadership Style has no significant effect on Employee Performance through Work Motivation. The results of testing the H7 hypothesis indicate that the work environment does not significantly affect employee performance through work motivation.